Development of iot furniture platform connected to smart home and application - Yoon Chun, Byung (International Journal of Engineering and Technology, 2018)
Background/Objectives: A practical use of sterilizer to prevent the inside of closet and drawer from going moldywill be expected to increase demand in sterilizer for earrings and accessories.Methods/Statistical analysis: Application design and software are developed in consideration of user convenience connected with IoT platform. Major performance and function are defined, including materialization of unit function, hardware platform and instrument development, and development of embedded S/W and mobile application.Findings: Application connected to closing and opening device based on IoT is developed not only to remotely monitor open and shut the door in closet or drawer but also to switch device remotely which controls ion generator and humidity but also to operate alarm device in case of opening door of closet or drawer forcibly.Improvements/Applications: Application as a smart lock for security can be expected in office, closet, and drawers. A practical use of sterilizer to prevent the inside of closet and drawer from going moldy is expected to using as a sterilizer for earrings and accessories.Â